Effects of Chemical and Physical Properties of Pond Bottom Sediments on Fish Rearing in Iraqi Kurdistan Region - Bayan Ahmed Abdulhlim; Mustafa Ismail Umer (Kufa Journal for Agricultural Sciences)
Some chemical and physical properties in soil- water interface in ponds of fish rearing in Duhok city Iraqi-Kurdistan    region in summer 2014 such as (redox potential, exchange acidity, total and active calcium carbonate, soil pH and salinity, cation exchange capacity, particle-size distribution, Olsen extractable phosphorus, water total alkalinity, hardness, dissolved oxygen and water-extractable phosphorus) were studied to determine the impacts of variation in these properties on the fish biology and survival in the pond. Result showed that the clayey and very low permeable of bottom soil of pond was a suitable condition for anaerobic respiration, as a result of producing organic acid and alcohol, formation of hydrogen sulfide, nitrite, manganese, ferrous iron, and methane that makes hard poisonous conditions which negatively affect on fish survival and growth, it reduced the concentration of dissolved oxygen in the water of pond to 5.96±1.0 (mgL-1)..In addition long days, (16 hour), and high temperature degree ,40-50C°, during summer season, and high fertilizing led to increase the accumulation of organic matter (%) 5.84± 1.53 that serve the raw material  of anaerobic respiration leading to high mortality and sensitivity to disease among fish in the pond.